Nature conservation volunteerism among school students - Lim, Evelyn Ai Lin; Wong, Li Juan; Bidin, Sheena; Mariapan, Manohar (Forestry Department Peninsular Malaysia, 2020)
Nature conservation volunteer programs promote active learning through direct involvement. Although many volunteering programs have been initiated, school students' involvement is still low. One of the reasons is the lack of volunteering programs that fit students' needs and motivation. Hence, the study determines students' motivation to be involved in a nature conservation program based on the Motivation-Opportunity-Ability model. The study utilized focus group discussion (FGD) to obtain the primary data. The FGD sessions involved forty-five (45) secondary school students. All discussions were audio-recorded and analyzed thematically. Findings showed that students have positive beliefs about being a volunteer in a nature conservation program. Their volunteering behavior is motivated by the desire to contribute towards the conservation of the conservation sites and the local community. They are also motivated to achieve personal development through knowledge gains, new experiences, self-confidence and being a role model to their friends and family. Parents, teachers, and friends are important people in influencing their volunteering behavior. The selection of time and non-monetary rewards facilitates their involvement. The availability and accessibility of the volunteer program is supported by task knowledge and familiarization of the implementation of the program.